THE IMPORTANCE OF CULTURE AS A BASIC TEACHING ENGLISH LANGUAGE IN CHILDHOOD IN INDONESIA - Ima Frafika Sari (Universitas Ahmad Dahlan)
This research aims at revealing: (1) the important of teaching culture in English language; (2) the important teaching culture for childhood; (3) the teaching English is important for childhood; (4) the teaching English is important in Indonesia; and how the age and duration of education in Indonesia. It is kinds of qualitative research which is aimed at revealing the important of teaching English language for early childhood in Indonesia. There are still lack of research about the important of teaching culture in English language, therefore, this research is significant tobe conducted. The finding of the research can be described as follows: First, cultural learning in the foreign language classroom touches three spheres: empathy and understanding, knowledge, and communicative skill. Second, learners will understand aspects of the foreign culture in the traditions of social anthropology. Third, young children being educated in English that is highlighted in this volume refers to the widespread belief that ‘younger is better’ when it comes to language learning. Fourth, the objective of English language teaching in Indonesia is to equip students with a working knowledge of the language. The last, in Indonesia the age begin to study in formal education is from the age 7 years old, and the duration is for 12 years.